The science of cheese - Tunick, Michael (New York : Oxford University Press, 2014)
"Experienced food scientist Michael Tunick details the chemistry and biology that go into cheese and its formation, as well as many other scientific aspects of dairy products. Tunick takes us back 8,000 years to the Fertile Crescent and shows us the accidental scientific discovery of cheese, when milk separated into curds and whey. We learn about milk allergies, lactose intolerance, and the reasons why cheese is vital to a balanced diet. Though he's spent 27 years studying the chemistry, biology, physics, nutrition, and even the climatology of cheese, Tunick writes for the non-scientific reader, providing an engaging and entertaining look at the science behind one of the world's favorite foods. The Science of Cheese reveals how, as much as cheese-making is a celebrated culinary art, it is an equally distinct scientific process."--Jacket.
In the beginning: milk -- Curds and whey : cheesemaking -- You're not getting older, you're getting better : aging cheese -- Fresh soft cheeses, acids, and safety -- Whey and pickled cheeses, amino and fatty acids, and salt -- Stretched curd cheeses, alcohols, and melting -- Surface mold cheeses, sulfur compounds, and the senses -- Smear-ripened cheeses, esters, and aroma -- Interior mold cheeses, ketones, and microbial strains -- Cheddared cheeses, aldehydes, and texture -- Washed curd cheeses, lactones, feed, and species -- Cheeses with eyes, furans, hydrocarbons, and food pairing -- Very hard cheeses, terpenes, and terroir -- Process cheeses and nutrition -- Analysis and flavor comparisons -- Laws, regulations, and appellations -- Do try this at home -- The cheese stands alone.
Includes bibliographical references (pages 247-271) and index.
Keywords: Cheesemaking; Cheesemaking; Ost; Cheesemaking